A study of the application of permeable pavements as a sustainable technique for the mitigation of soil sealing in cities: A case study in the south of Spain. (1st January 2018) - Rodríguez-Rojas, M.I.; Huertas-Fernández, F.; Moreno, B.; Martínez, G.; Grindlay, A.L.
Abstract: The use of 'Sustainable Urban Drainage Systems' (SuDS) has become a more sustainable alternative for managing stormwater, greatly reducing the effects of soil sealing. However, the lack of monitored projects is a barrier to their implementation, as the companies which manage sewer systems cannot quantify the impact and cost-efficiency of SuDS. This paper presents a project developed in the south of Spain, in which the hydrological performance of 3 types of permeable pavements has been analyzed. The efficiencies obtained (over 70%), are higher than or similar to the efficiencies of vegetated SuDS, demonstrating the capacity of these pavements for delaying catchment area response and slow flow velocities, reducing the operating costs of sewer systems and the flood risk, while also ensuring service conditions for cities and safety for pedestrian and vehicular circulation. This pilot site has generated results which are sufficiently consistent so as to be representative, and serve as a reference for other cities with a similar climate. Highlights: It has been demonstrated that the permeable pavements have very good hydraulic performance. The permeable pavements tested were capable of absorbing almost the total rainfall. The efficiencies of permeable pavements (over 70%), are higher than or similar to than the efficiencies of vegetated SuDS. These pavements are able to reduce flood risk and improve the exploitation of sewerage system. The results of this research will be the base for the design of these systems in the south of Spain.